Development of a quadruplex real-time quantitative RT-PCR for detection and differentiation of PHEV, PRV, CSFV, and JEV - Hu, Xin; Feng, Shuping; Shi, Kaichuang; Shi, Yuwen; Yin, Yanwen; Long, Feng; Wei, Xiankai; Li, Zongqiang (Frontiers in Veterinary Science, 2023)
Porcine hemagglutinating encephalomyelitis virus (PHEV), porcine pseudorabies virus (PRV), classical swine fever virus (CSFV), and Japanese encephalitis virus (JEV) cause similar neurological symptoms in the infected pigs, and their differential diagnosis depends on laboratory testing. Four pairs of specific primers and probes were designed targeting the PHEV N gene, PRV gB gene, CSFV 5′ untranslated region (5’UTR), and JEV NS1 gene, respectively, and a quadruplex real-time quantitative RT-PCR (qRT-PCR) was developed to detect and differentiate PHEV, PRV, CSFV, and JEV. The assay showed high sensitivity, with the limit of detection (LOD) of 1.5 × 101 copies/μL for each pathogen. The assay specifically detected only PHEV, PRV, CSFV, and JEV, without cross-reaction with other swine viruses. The coefficients of variation (CVs) of the intra-assay and the inter-assay were less than 1.84%, with great repeatability. A total of 1,977 clinical samples, including tissue samples, and whole blood samples collected from Guangxi province in China, were tested by the developed quadruplex qRT-PCR, and the positivity rates of PHEV, PRV, CSFV, and JEV were 1.57% (31/1,977), 0.35% (7/1,977), 1.06% (21/1,977), and 0.10% (2/1,977), respectively. These 1,977 samples were also tested by the previously reported qRT-PCR assays, and the coincidence rates of these methods were more than 99.90%. The developed assay is demonstrated to be rapid, sensitive, and accurate for detection and differentiation of PHEV, PRV, CSFV, and JEV.